Osteoporosis in men - Ebeling, Peter R. (Henry Stewart Talks, 2015)
Epidemiology and mechanisms of bone loss in men, Hip fractures in men, Role of IGF-I and sex hormones in bone loss, Bone fractures in obese/overweight men, Review of the endocrine society guidelines on osteoporosis in men, Assessing risk factors for osteoporosis in men, Review of osteoporosis treatments, Gaps in evidence base